Influence of the electrolyte's pH on the properties of electrochemically deposited hydroxyapatite coating on additively manufactured Ti64 alloy. Issue 1 (December 2017) - Vladescu, Alina; Vranceanu, Diana; Kulesza, Slawek; Ivanov, Alexey; Bramowicz, Mirosław; Fedonnikov, Alexander; Braic, Mariana; Norkin, Igor; Koptyug, Andrey; Kurtukova, Maria; Dinu, Mihaela; Pana, Iulian; et al.
Abstract Properties of the hydroxyapatite obtained by electrochemical assisted deposition (ED) are dependent on several factors including deposition temperature, electrolyte pH and concentrations, applied potential. All of these factors directly influence the morphology, stoichiometry, crystallinity, electrochemical behaviour, and particularly the coating thickness. Coating structure together with surface micro- and nano-scale topography significantly influence early stages of the implant bio-integration. The aim of this study is to analyse the effect of pH modification on the morphology, corrosion behaviour andin vitro bioactivity andin vivo biocompatibility of hydroxyapatite prepared by ED on the additively manufactured Ti64 samples. The coatings prepared in the electrolytes with pH = 6 have predominantly needle like morphology with the dimensions in the nanometric scale ( 30 nm). Samples coated at pH = 6 demonstrated higher protection efficiency against the corrosive attack as compared to the ones coated at pH = 5 ( 93% against 89%). Thein vitro bioactivity results indicated that both coatings have a greater capacity of biomineralization, compared to the uncoated Ti64. Somehow, the coating deposited at pH = 6 exhibited good corrosion behaviour and high biomineralization ability.In vivo subcutaneous implantation of the coated samples into the white rats for up to 21 days with following histological studies showed no serious inflammatory process.